Joint Investigation and 3D Visual Evaluation of Rock Mass Quality. (30th December 2020) - Yuan, Haiping; Chen, Chenghao; Wang, Yixian; Bian, Hanbing; Liu, Yan
Abstract : In order to realize the high efficiency quality classification and three-dimensional visualization of engineering rock mass and to solve the technical difficulties of the traditional rock mass quality evaluation method such as high labor intensity, long process time consumption, many intervention processes such as scale measurement and manual calculation, and nonintuitive classification results, this paper puts forward a 3D visual rock mass quality evaluation method and system based on close-range photography, which optimizes the traditional rock mass quality evaluation method, makes the rock mass classification three-dimensional and visible, and realizes the estimation of unrevealed rock mass quality evaluation index. The research results show the following: (1) The method of storing joint information by close-range photography and extracting joint information by human-computer interaction improves the working efficiency and the process is safe and controllable compared with the traditional method of collecting fracture parameters. (2) Based on the statistical analysis of 97 groups of roadway survey data, the comprehensive statistical regression formula between BQ value of Chinese national standard and RMR value is given, and there is a good correlation between BQ value and RMR value of rock mass quality index. (3) Based on the power-inverse ratio method, the three-dimensional model of rock mass classification of the mine was established, and the cutting model obtained the current distribution diagram of rock mass quality grade, providing scientific reference for drilling, blasting, support, and other production design optimizations.